Kendali Komunikasi Tim Produksi Program “Tikaudjo” pada Radio Bahana 101.8 FM Jakarta - Ketut Wiriyanto; Ahmad Toni (JURNAL LENSA MUTIARA KOMUNIKASI, 2021)
This study aims to determine the organizational control team of the TikaUdjo production program. The proposed research statement is what the organization controls on the TikaUdjo program production team. The theory that researchers use to obtain data uses organizational control theory. The research method used is a descriptive qualitative approach with a post-positivism paradigm. The research subjects are producers, assistant producers and broadcasters in obtaining accurate data, and the object of research is the control of the production team of the TikaUdjo program organization on Bahana Radio 101.8 FM Jakarta. Collecting data obtained through in-depth interviews and participant observation conducted on key informants and informants. Other data were obtained from Key Informants, informants, and various other data sources. The results of this study indicate that the TikaUdjo program production team at Radio Bahana 101.8 FM Jakarta consistently implements four concepts of organizational control theory by Phillip Tompkins, George Cheney, and their colleagues. The conclusion of this research is that the production team performs the four control theory concepts quite well, and it can be accounted for in which these four theoretical concepts are the processes that the production team does in producing the event program.